Digitalisation: Channels, impacts and implications for monetary policy in the euro area (European Central Bank (ECB), 2021)
The digitalisation workstream report analyses the degree of digital adoption across the euro area and EU countries and the implications of digitalisation for measurement, productivity, labour markets and inflation, as well as more recent developments during the coronavirus (COVID-19) pandemic and their implications. Analysis of these key issues and variables is aimed at improving our understanding of the implications of digitalisation for monetary policy and its transmission. The degree of digital adoption differs across the euro area/EU, implying heterogeneous impacts, with most EU economies currently lagging behind the United States and Japan. Rising digitalisation has rendered price measurement more challenging, owing to, among other things, faster changes in products and product quality, but also new ways of price setting, e.g. dynamic or customised pricing, and services that were previously payable but are now 'free'. Despite the spread of digital technologies, aggregate productivity growth has decreased in most advanced economies since the 1970s. However, it is likely that without the spread of digital technologies the productivity slowdown would have been even more pronounced, and the recent acceleration in digitalisation is likely to boost future productivity gains from digitalisation. Digitalisation has spurred greater automation, with temporary labour market disruptions, albeit unevenly across sectors. The long-run employment effects of digitalisation can be benign, but its effects on wages and labour share depend on the structure of the economy and its labour market institutions. The pandemic has accelerated the use of teleworking: roughly every third job in the euro area/EU is teleworkable, although there are differences across countries. ...
Keywords: E24; E31; E32; O33; O57; 330; measurement; productivity; labour markets; inflation; COVID-19